GAMBARAN FAKTOR RISIKO PENYAKIT JANTUNG KORONER PADA USIA MUDA DI RSUP DR. M. DJAMIL PADANG TAHUN 2017-2019 - Jamil, Muhammad Irfan; Yanni , Mefri; Noer , Mustafa (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Coronary heart disease (CHD) is a coronary atherosclerotic disease which refers to a pathological process that affects the coronary arteries. In general, there are two types of risk factors for coronary heart disease, namely risk factors that cannot be modified and risk factors that can be modified. Non-modifiable risk factors are age, gender, and genetics. Modifiable risk factors are hypertension, hypercholesterolemia, hypertriglyceridemia, diabetes mellitus, smoking, obesity, lack of activity, and stress. The purpose of this study was to describe the risk factors for coronary heart disease at a young age. This type of research is a descriptive study using a cross-sectional study design from secondary data of medical records of patients with coronary heart disease at Dr. RSUP. M. Djamil Padang in 2017-2019 with a total sample of 61 people. The results showed that there were 47 male patients (77.05%) and 14 female patients (22.95%). For patients who have a family history of risk factors as many as 3 people (4.9%), hypertension as many as 30 people (49.18%), hypercholesterolemia as many as 12 people (19.67%), hypertriglycerides as many as 10 people (16.39%) , diabetes mellitus as many as 10 people (16.39%), obesity as many as 5 people (8.2%), and smoking as many as 16 people (26.23%). The conclusion of this study is there were 61 patients with CHD at a young age in 2017-2019, the risk factors for CHD patients at a young age were mostly at the age of 26-45 years, followed by male gender, risk factors for hypertension, risk factors for smoking, risk factors for hypercholesterolemia, risk factors for hypertriglycerides, risk factors for diabetes mellitus, risk factors for obesity, and risk factors for family history.